Semi-autonomous flying robot for physical interaction with environment - Albers, Albert; Trautmann, Simon; Howard, Thomas; Trong Anh Nguyen; Frietsch, Markus; Sauter, Christian (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
This contribution presents the first results of the development of an unmanned aerial vehicle (UAV) which is capable of applying force to a wall while maintaining flight stability. This is a novel idea since UAVs are used so far only for tasks without physical contact to the surrounding objects. The basis for the work presented is a quadrotor system which is stabilized with an inertial measurement unit. As a new approach an additional actuator was added to generate forces in physical contact while the UAV stays horizontal. A control architecture based on ultrasonic distance sensors and a CMOS-camera is proposed. The performance of the system was proved by several flight tests. Potential applications of the system can be physical tasks at high places like cleaning windows or walls as well as rescue or maintenance tasks.